2013
DOI: 10.1186/1471-244x-13-197
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility (risk and protective) factors for in-patient violence and self-harm: prospective study of structured professional judgement instruments START and SAPROF, DUNDRUM-3 and DUNDRUM-4 in forensic mental health services

Abstract: BackgroundThe START and SAPROF are newly developed fourth generation structured professional judgement instruments assessing strengths and protective factors. The DUNDRUM-3 and DUNDRUM-4 also measure positive factors, programme completion and recovery in forensic settings.MethodsWe compared these instruments with other validated risk instruments (HCR-20, S-RAMM), a measure of psychopathology (PANSS) and global function (GAF). We prospectively tested whether any of these instruments predict violence or self har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
79
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(95 citation statements)
references
References 40 publications
(64 reference statements)
11
79
4
Order By: Relevance
“…In contrast to some studies of relapses by former prisoners released into the community or prisoners in psychiatric facilities (Abidin et al, 2013;deVries Robbé, deVogel, Koster, et al, 2015), we did not obtain incremental values of any scales or subscales that showed fair to good AUC values. This is in line with recent studies suggesting that despite differences in the theoretical bases underlying the four instruments, they tend to measure the same core construct (Yang et al, 2010).…”
Section: Predictive Validity Comparisons For Physically Violent Miscontrasting
confidence: 99%
“…In contrast to some studies of relapses by former prisoners released into the community or prisoners in psychiatric facilities (Abidin et al, 2013;deVries Robbé, deVogel, Koster, et al, 2015), we did not obtain incremental values of any scales or subscales that showed fair to good AUC values. This is in line with recent studies suggesting that despite differences in the theoretical bases underlying the four instruments, they tend to measure the same core construct (Yang et al, 2010).…”
Section: Predictive Validity Comparisons For Physically Violent Miscontrasting
confidence: 99%
“…Co-occurrence of aggression against the self and others has been previously illustrated in violent psychiatric inpatients (46). Indeed, research has identified an overlap in the factors predictive of the risk of violence towards others and the risk of self-harm (46)(47)(48). Similar to our findings, these studies identified a history of self-harm to be strongly predictive of future violence to others (46)(47)(48) and highlighted the relevance of jointly managing both issues in forensic populations.…”
Section: [Table 5 Somewhere Here]supporting
confidence: 88%
“…One of these gaps involves whether persons who deliberately self-harm are violent toward others. Several studies allude to aggression (Haavisto et al, 2005) and one study has found that among psychiatric inpatients self-harm and violence are correlated and share common risk and protective factors (Abidin et al, 2013). Beyond these studies, little research has accrued on the connection between DSH behaviors and violent behaviors, including cruelty to animals.…”
Section: Study Aimsmentioning
confidence: 98%